Computational modeling of protein diffusion in the cell nucleus using the lattice-Boltzmann method - Filippovych, Kateryna (2012)
The number of fluorescence applications and methods of analysis is growing in the biological and related sciences. The aim of this work was to accurately determine the diffusion coefficient in nucleus, diffusion in the cytoplasm and nucleo-cytoplasmic translocation should be considered as well. Fluorescence recovery after photobleaching (FRAP) experiments were used in order to study protein diffusion. A numerical model for FRAP was used to determine the diffusion properties of proteins. The present method removed the difficulties of the conventional analysis, could produce, interesting results for protein diffusion in the cell.